Fractional amplitude of low-frequency fluctuations is disrupted in Alzheimer's disease with depression. Issue 7 (July 2017) - Guo, Zhongwei; Liu, Xiaozheng; Li, Jiapeng; Wei, Fuquan; Hou, Hongtao; Chen, Xingli; Li, Xinwei; Chen, Wei
Highlights: Depression can reduce cognitive function in Alzheimer's disease (AD). AD with depression exhibited higher fALFF in several brain regions, including fusiform gyrus, caudate nucleus, and middle temporal gyrus, and lower fALFF in the supplementary motor area. This pattern might be an important neuropathophysiologic characteristic of depression in AD. Abstract: Objective: To explore brain activity in AD with depression (D-AD) based on fractional amplitude of low-frequency fluctuation (fALFF). Methods: Twenty-two D-AD and 21 AD without depression patients (nD-AD) were examined by magnetic resonance imaging during resting state. Neuropsychiatric Inventory and Hamilton Depression Rating Scale were employed to assess the severity of depression. We analysed the characteristics of fALFF in D-AD differing from nD-AD. We also examined the correlation between fALFF and the depression severity. Results: D-AD patients had higher fALFF in right fusiform gyrus, left caudate nucleus, and right middle temporal gyrus (MTG), meanwhile lower fALFF in supplementary motor area (SMA) than nD-AD patients. Conclusions: Abnormal fALFF changes in fusiform gyrus, caudate nucleus, MTG and SMA may be important neuropathophysiologic characteristics of depression in AD. Significance: We have clarified the potential neuropathological changes of depression in AD based on fALFF method, which is crucial for effective intervention.